Folk dolls as a universal object in psychotherapeutic work with women - Bochkarjova, Іolanta; Zaichikova, Т. (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2017)
The article is devoted to the analysis of the potential of Slavic rag doll in modern psychotherapeutic practice (Doll-therapy, the method of Art- therapy). It examines the phenomenon of ethnic dolls as psychotherapeutic object, as well as shows the versatility of slavic dolls in therapeutic practice of psychodynamic approach, Jung's analysis, transactional analysis and Gestalt-therapy. A folk doll represents a unique tool in psychotherapeutic work with women.
Keywords: folk doll; Doll-therapy; a universal symbol; woman; psychotherapeutic object